Party Primaries, Candidate Selection and Intra-Party Conflict in Nigeria: PDP in Perspective - Adekeye, Muinat Adetayo (Covenant University Journal of Politics and International Affairs, 2017)
This paper underscores the interplay among party primaries, candidate selection and intra-party conflicts in the People‟s Democratic Party(PDP). It employs the theoretical explanations of the Group Conflict Theory which posits that conflicts within groups are borne out of incompatible interests catalyzed by selfish nature of individuals. Findings from the qualitative analysis signifies that while institutional structures have been enacted to avert conflicts within the party, non-adherence to the dictates of such structures have birthed a wide range of internal conflicts within the party, thus resulting to cases of defection, factionalization, proliferation of political parties, unconstitutional change of party leaders and most importantly, the defeat of the party in 2015 general elections. It was recommended that effective restructuring of internal laws and polices within PDP, establishment of punitive measure and the practice of transparency by the INEC would ensure good governance in Nigeria.